Late Eocene to early Oligocene productivity events in the proto-Southern Ocean and correlation to climate change - G. Rodrigues de Faria; D. Lazarus; J. Renaudie; J. Stammeier; V. Özen; U. Struck (Climate of the Past, 2024)
The Eocene–Oligocene transition (EOT, ca. 40–33 Ma ) marks a transformation from a largely ice-free to an icehouse climate mode that is well recorded by oxygen-stable isotopes and sea surface temperature proxies. Opening of the Southern Ocean gateways and decline in atmospheric carbon dioxide levels have been considered as factors in this global environmental transformation and the growth of ice sheets in Antarctica during the Cenozoic. A more comprehensive understanding is still needed of the interplay between forcing versus response, the correlation among environmental changes, and the involved feedback mechanisms. In this study, we investigate the spatio-temporal variation in export productivity using biogenic Ba (bio- Ba ) from Ocean Drilling Program (ODP) sites in the Southern Ocean, focusing on possible mechanisms that controlled them as well as the correlation of export productivity changes to changes in the global carbon cycle. We document two high export productivity events in the Southern Ocean during the late Eocene (ca. 37 and 33.5 Ma ) that correlate to proposed gateway-driven changes in regional circulation and to changes in global atmospheric p CO 2 levels. Our findings suggest that paleoceanographic changes following Southern Ocean gateway openings, along with more variable increases in circulation driven by episodic Antarctic ice sheet expansion, enhanced export production in the Southern Ocean from the late Eocene through early Oligocene. These factors may have played a role in episodic atmospheric carbon dioxide reduction, contributing to Antarctic glaciation during the Eocene–Oligocene transition.